A new genus and species of spring snails (Caenogastropoda, Tateidae) from the ultramafic South of New Caledonia - Ove Schröder; Peter M. Schächinger; Philippe Bouchet; Martin Haase (European Journal of Taxonomy)
During an expedition in 2016, a rich fauna of freshwater gastropods of the family Tateidae Thiele, 1925 was discovered on the ultramafic terrains of the Southeast of New Caledonia (NC). Hitherto, only three of the 62 known NC family members were reported from this type of bedrock. With less than 1.5 mm in length, many of the new species are particularly small. In order to establish a methodological setup for the description and phylogenetic analyses of these new species, we here describe Viriiella touaouroua gen. et sp. nov. and assess its relationships based on three gene fragments. Viriiella is morphologically well defined and resembles Fluviopupa Pilsbry, 1911 not present in NC. In the phylogenetic analyses, though, Viriiella appeared as a member of the Hemistomia-clade, the NC tateids occurring on non-ultramafic terrain. However, Viriiella had the longest branch and, sister group to different genera in maximum likelihood and Bayesian analyses, its position was unstable, probably an artifact due to long-branch attraction. Considering that Viriiella does not share the defining character states of Hemistomia s. lat., it may well be possible that inclusion of more related genera will show that the new taxa share a most recent common ancestor with the Hemistomia-clade, but as sister group.